Electrostatically confined Bi/Ti3C2Tx on a sponge as an easily recyclable and durable catalyst for the reductive transformation of nitroarenes. Issue 35 (26th May 2021) - Yu, Changqiang; Peng, Linfen; Zhu, Yisong; Xie, Guanshun; Wu, Zhenjun; Xie, Xiuqiang; Zhang, Nan
Abstract : Bi/Ti3 C2 T x has been electrostatically confined on a porous bulk sponge, which exhibits enhanced activity and improved durability for the catalytic reduction of nitroarenes compared to the counterpart of Bi/reduced graphene oxide. Abstract : Developing novel catalysts with both easily accessible recyclability and long-term durability toward chemical synthesis is highly desirable yet remains to be explored. In this work, a porous and bulk sponge-confined bismuth (Bi)/Ti3 C2 T x (MXene) composite as a monolithic catalyst is synthesized via the photodeposition of Bi nanoparticles with a mean size of 4.4 nm on Ti3 C2 T x followed by electrostatic self-assembly between the negatively charged Bi/Ti3 C2 T x and positively charged sponge. It is noteworthy that compared to the analogue of widely investigated reduced graphene oxide, Ti3 C2 T x with favorable hydrophilic surface groups as the scaffold for the high dispersion of Bi nanoparticles benefits not only efficient aqueous phase catalytic reactions, but also strong electrostatic interaction with the sponge substrate for ensuring the recyclability towards practical applications. As a result, the bulk sponge-confined Bi/Ti3 C2 T x as an easily recyclable catalyst possesses both improved catalytic performance and long-term durability for the hydrogenation of nitroarenes in the aqueous phase. This study presents a facile and valuable protocol for functionalizing inexpensively available porous bulk materials to confine catalysts towards integrated materials featuring easy-separation and long-term stability for practical catalytic processes.